Karakteristik Fisik, Kimia, dan Sensori Flakes Berbasis Tepung Uwi Ungu (Dioscorea alata L.) dengan Penambahan Tepung Kacang Kedelai (Glicyn max L.): Physical, Chemical and Sensory Characteristics of Flakes Based on Purple Yam Flour (Dioscorea alata L.) with Addition of Soybean Flour (Glicyn max L.) - Distya Rizki Hapsari; Aulia Rizki Maulani; Siti Aminah (JURNAL AGROINDUSTRI HALAL, 2022)
Flakes are a practical breakfast menu that generally contains nutrients in the form of carbohydrates, and protein, rich in fiber, vitamins, and minerals to meet the nutritional intake of the morning. This study aims to make flakes purple yam with the addition of soybean flour to increase its nutritional value, especially protein content. This study used a Completely Randomized Design (CRD) with one factor, namely the ratio of purple yam flour and soybean flour (100% : 0%), (90% : 10%), (80% : 20%), (70% : 30 %). Product analysis includes protein content, water content, and rehydration power (physical) to determine the selected product, then chemical analysis includes ash content, fat, crude fiber, and carbohydrates, as well as sensory and hedonic quality organoleptic tests. The data analysis used was ANOVA and Duncan's Advanced Test with 95% confidence interval. The results showed that the flakes selected were treated with 70% purple yam and 30% soybean flour. The flakes selected have protein content of 15.62%, water content of 4.40%, ash content of 1.55%, fat 4.16%, crude fiber 13.53%, carbohydrates 74.47%, and rehydration power of 18.84%. The results of the sensory quality test showed that the flakes had a dark brown color, odorless powdery aroma, slightly sweet taste, and a crunchy texture. The results of the hedonic test have the highest preference value on the attributes of texture, color, and aroma and, overall, towards liking.